Treatment of hypertriglyceridemia: a review of current options - Vrablík, M; Češka, R (Physiological research, 2015)
Hypertriglyceridemia is an important marker of increased levels of highly atherogenic remnant-like particles. The importance of lowering plasma levels of triglycerides (TG) has been called into question many times, but currently it is considered an integral part of residual cardiovascular risk reduction strategies. Lifestyle changes (improved diet and increased physical activity) are effective TG lowering measures. Pharmacological treatment usually starts with statins, although associated TG reductions are typically modest. Fibrates are currently the drugs of choice for hyperTG, frequently in combination with statins. Niacin and omega-3 fatty acids improve control of triglyceride levels when the above measures are inadequately effective. Some novel therapies including anti-sense oligonucleotides and inhibitors of microsomal triglyceride transfer protein have shown significant TG lowering efficacy. The current approach to the management of hypertriglyceridemia is based on lifestyle changes and, usually, drug combinations (statin and fibrate and/or omega-3 fatty acids or niacin).
Keywords: Hypertriglyceridemia; Triglycerides; omega-3 mastné kyseliny; chování snižující riziko; výsledek terapie; Risk Reduction Behavior; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Fatty Acids, Omega-3; zvířata; Humans; Randomized Controlled Trials as Topic; statiny; hypolipidemika; triglyceridy; Niacin; hypertriglyceridemie; rizikové faktory; Hypolipidemic Agents; randomizované kontrolované studie jako téma; Risk Factors; niacin; Treatment Outcome; lidé; Animals